How do Agricultural Journalists Write? Social And Cognitive Behaviors Of a Specialized Writing Process - Jean O'Brien Elefson (Journal of Applied Communications, 1992)
A lack of theory, models, and methods in the agricultural science news writing process spurred the initial investigation of this specialized writing process.